The greatness mindset : unlock the power of your mind and live your best life today - Howes, Lewis, 1983- (Hay House, Inc., 2023)
"Greatness is inside you. Now is the time to wake it up. Are you living your most authentic life? Are you leaning into your purpose or running away from it? Is this the story you want your future self to tell or do you ache for something more? Through his breakthrough discoveries, New York Times best-selling author Lewis Howes reveals how you can rewrite your past to propel yourself into a powerful and abundant future. With these raw and revealing personal stories, science-backed strategies from industry-leading experts, and step-by-step guidance, you will learn how to: Clearly define a Meaningful Mission to enhance your purpose for this season of life; Identify the root causes of self-doubt and conquer the fears that hold you back; Transform your mind to end self-sabotaging thoughts to live a rich life; Manifest your greatness to make the maximum positive impact on those around you. By applying the lessons and strategies found inside The Greatness Mindset, you will be able to design the life of your dreams and turn it into reality. Are you ready? Your journey to greatness begins now!"--Dust jacket flap.